Tepa Selira: Toward a Javanese Empathetic Epistemology of Interfaith Knowledge - Rofikasari Mutmainah; Alfan Nawaziru Zahara; Lailatul Romadhina; Adib Khairil Musthafa (Civiliza Publishing, 2026)
This article discusses interfaith literacy in Indonesian Islamic education through a decolonial critique of modern religious epistemological framework. Current discussions on religious literacy and interreligious literacy have contributed significantly to shifting religious education beyond doctrinal and essentialist approaches toward more historical, social, and contextual understandings of religion. Yet these frameworks often continue to approach religious difference through liberal-secular categories shaped by Western historical experiences. Consequently, other religions are frequently positioned as objects to be classified, interpreted, and managed rather than as subjects participating in the production of knowledge about themselves. Using library research and a critical conceptual review approach, this article analyzes recent scholarship on religious literacy, interreligious literacy, liberal pluralism, coloniality of knowledge, and Javanese local epistemologies. The study finds that interfaith literacy in Indonesian Islamic education is commonly framed within agendas of religious moderation and counter-radicalization, leading interfaith engagement to function primarily as an instrument of social stability and governance. Against this tendency, the article turns to tepa selira as a Javanese epistemic framework grounded in rasa, reflexivity, representational humility, and attentiveness toward the position of others. Rather than treating tepa selira merely as local wisdom or cultural ethics, the article situates it as a relational mode of knowing capable of rethinking how religious others are approached within Islamic education. Through this perspective, interfaith literacy is reoriented from “knowing about the religious other” toward “knowing with ethical responsibility toward the religious other.” In doing so, the article contributes to broader debates on decolonial education by demonstrating how Indonesian Islamic education can become a site for producing alternative epistemologies from the Global South rather than merely applying Western models of religious literacy.